The efficacy of controlled stepped intracranial decompression surgery in patients with craniocerebral injury - Huang, Xiaobin; Yu, Cheng; Liao, Xiaoyue; Dong, Baizhuo; Zheng, Jun; Zhang, Shanchi (Frontiers in Neurology, 2025)
BackgroundHead injuries are frequently the result of high-energy trauma, which is often severe and has a high mortality rate.MethodsThis retrospective study included 78 patients with severe traumatic brain injury treated from January 2021 to January 2023. Patients were divided into two groups: a control group (n = 33) treated with standard large bone flap decompression, and a research group (n = 45) treated with controlled stepwise intracranial decompression. Surgical parameters, treatment efficacy, complications, neurological function, and serum biomarkers (IL-6, CRP, NSE) were compared. Multivariate logistic regression was adjusted for confounders received.ResultsThe research group had significantly shorter decompression initiation times, reduced operation durations, and less intraoperative blood loss (p < 0.05). The effective treatment rate was higher in the research group (80.0% vs. 57.6%, p < 0.05). After treatment, both groups showed improvements in NFD and GCS scores, with more significant improvement in the research group (p < 0.01). Inflammatory markers (IL-6, CRP, NSE) decreased post-treatment in both groups, with significantly lower levels in the research group (p < 0.01). The complication rate was markedly lower in the research group (8.9% vs. 30.3%, p < 0.05). Multivariate analysis confirmed that stepwise decompression was associated with higher clinical efficacy (aOR = 3.20, 95% CI: 1.24–8.28, p = 0.016) and fewer complications (aOR = 0.24, 95% CI: 0.07–0.82, p = 0.022). treatment, and NSE levels of the two groups were less than those after therapy (p < 0.05); and the blood IL-6, CRP, and NSE levels of the research group after treatment were greater than those of the control group.ConclusionControlled stepped intracranial decompression surgery could effectively shorten the operation time of sufferers with severe craniocerebral injury, reduce intraoperative blood loss, improve clinical treatment effects, improve patient prognosis, and promote neurological recovery.